A Control Strategy of Energy Storage Converter Based on Dual-droop Control for Onboard DC-grid - XU Rong; WANG Yue; PAN Gaofeng; HONG Xuewu; DENG Jianhua; ZHAO Haibin (Kongzhi Yu Xinxi Jishu)
Aiming at the requirements of precise power distribution/transfer between bi-directional DC-DC converters, DC-DC converter and diesel generator converter, as well as connected/islanded seamless transition with onshore DC-grid, it proposed a P-V and SOC-I based dual-droop control method for DC-DC converter. Buck-Boost dual-mode is employed to implement the bi-directional operation control of the energy storage batteries, and carrier phase-shift modulation can reduce the parallel-output current ripples of the multiple DC-DC converter. Simulation results verify the feasibility of the dual-droop control strategy.